2023
DOI: 10.1128/mra.01083-22
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Enterococcus faecium, Enterococcus gallinarum, and Lactococcus lactis Strains Isolated from a Mastitis-Infected Camel in Isiolo County, Kenya

Abstract: We report the draft genome sequences and annotation of Enterococcus faecium , Enterococcus gallinarum , and Lactococcus lactis isolates that were recovered from a mastitis-infected camel in Isiolo County, Kenya. Collectively, these data provide an invaluable repository for data mining to support the development of a potential multicomponent mastitis subunit vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, we have designed and computationally evaluated a novel, multi-epitope vaccine candidate for camel mastitis comprised of 9 CTL MHC-1 binding epitopes and 1 interferon-γ inducing HTL epitope obtained from selected antigenic protein sequences of local isolates of S. agalactiae and S. aureus (Murungi et al, 2022; Maichomo et al, 2023), the predominant camel mastitis causing bacteria (Younan et al, 2001; Seligsohn et al, 2021a; Seligsohn et al, 2021b). In silico simulations revealed the vaccine construct as capable of strongly stimulating the host innate and adaptive immune responses as evidenced by the elevated synthesis of IgM, IgG, cytokines, macrophages, dendritic cells and natural killer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have designed and computationally evaluated a novel, multi-epitope vaccine candidate for camel mastitis comprised of 9 CTL MHC-1 binding epitopes and 1 interferon-γ inducing HTL epitope obtained from selected antigenic protein sequences of local isolates of S. agalactiae and S. aureus (Murungi et al, 2022; Maichomo et al, 2023), the predominant camel mastitis causing bacteria (Younan et al, 2001; Seligsohn et al, 2021a; Seligsohn et al, 2021b). In silico simulations revealed the vaccine construct as capable of strongly stimulating the host innate and adaptive immune responses as evidenced by the elevated synthesis of IgM, IgG, cytokines, macrophages, dendritic cells and natural killer cells.…”
Section: Resultsmentioning
confidence: 99%
“…have been isolated from camel udders (Zeryehun and Abera, 2017), the highly infective Streptococcus agalactiae (group B Streptococcus ) is the main mastitis causing bacteria. Our recent studies (Ochieng et al, 2021; Murungi et al, 2022; Maichomo et al, 2023) have identified several bacterial strains that potentially cause camel mastitis in Kenya. Given the indiscriminate use of antibiotics for the treatment of mastitis against the backdrop of global antimicrobial resistance (Naranjo-Lucena and Slowey, 2023), development of effective vaccines for camel mastitis is a pressing critical need.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important in current times when antimicrobial resistance is a global issue and strategies are being formulated to address this challenge. Whole-genome sequencing (WGS) of several species of enterococcus isolated from mastitic milk from camels in Kenya has been carried out including the genomes of E. faecalis strain 1351 [7], E. faecium and E. gallinarum [6], E raffinosus CX012922 isolated from patient's fecal samples [85] and E. casseliflavus strain UFMG-H8 [86] isolated from the urine of healthy bovine heifers. Many more studies have carried out WGS on many species of enterococcus.…”
Section: Genomics Of Enterococcusmentioning
confidence: 99%
“…In Africa, various enterococcus species have been identified, including E. casseliflavus, E. faecalis, E. durans, E. gallinarum, E. thailandicus, E. devriesei, E. faecium, E. hirae, and E. mundtii [6][7][8][9]. Since enterococci are part of the microbiota of many raw and non-sterilized food products, presence does not necessarily imply direct fecal contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation